Efeito do hidrolisado de clara de ovo como possível protetor das alterações no sistema cardiovascular promovidas pela exposição ao Cloreto de Cádmio em ratos - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Introduction: Cadmium (Cd) is a heavy metal that we are easily exposed through the consumption of drinking water, food and cigarette smoke. Its deleterious effects affect several organs and systems, and the cardiovascular system is one of the affected. In contrast, functional foods derived from animal proteins have been investigated as an alternative or complementary treatment for innumerable pathologies, including oxidative, inflammatory and metabolic damages caused by heavy metals, bypassing these effects through bioactive peptides. Objective: To investigate whether egg White hydrolyzate (EWH), a functional food, may be effective in combating cardiovascular damage caused by exposure to Cd. Materials and Methods: Male Wistar rats were treated for 14 days with: A ) Untreated group - intraperitoneal (ip) injections of distilled water and potable water by gavage; B) Group Cd - injections (i.p.) 1mg / kg of body weight / day of cadmium chloride (CdCl2) and potable water by gavage; C) EWH Group - Injections (i.p.) of distilled water and 1 mg / kd / day of pepsin EWH for 8 hours diluted in running water by gavage; D) CdEWH Group - both treatments. After treatment, systolic blood pressure (SBP) was measured by tail plethysmography; Vascular reactivity experiments in the aorta were performed in an organ bath, where the vasopressin dependent and endothelial independent responses were analyzed and the vasoconstricting response to phenylephrine (Phe) in the absence and presence of endothelium, and an inhibitor of NOS - ( L-NAME), an inhibitor of NADPH oxidase (apocynin), a non-selective COX inhibitor (indomethacin), a selective COX-2 inhibitor (NS 398), an AT-1 (losartan) receptor blocker. In situ expression of COX-2 protein was also performed in the aorta, while the determination of angiotensin converting enzyme (ACE) activity was measured in plasma. Levels of lipid peroxidation, reactive oxygen species (ROS) and antioxidant capacity (FRAP) were measured in pots. Results: EWH prevented the increase in SBP and vascular reactivity caused by Cd. These vascular improvements were related to the inhibition of COX-2 derived prostanoids by the reduction of expression of this protein, inhibition of angiotensin II by the reduction of ACE activity and consequent reduction of oxidative stress mediated by NADPH oxidase. Conclusion: EWH could be considered as an alternative for the treatment of cardiovascular damage induced by Cd.
Effect of egg white hydrolyzate as a possible protector of changes in the cardiovascular system promoted by exposure to Cadmium Chloride in rats
Keywords: Hipertensão; Reatividade vascular; Disfunção vascular; Estresseoxidativo; Hidrolisado de clara de ovo; Peptídeos bioativos; Cádmio; Hypertension; Vascular reactivity; Vascular dysfunction; Oxidative stress; Egg white hydrolyzate; Bioactive peptides; Cadmium; CNPQ::CIENCIAS BIOLOGICAS